Fertility preservation for young adults, adolescents, and children with cancer. (2nd April 2020) - Rodriguez-Wallberg, Kenny A.; Anastacio, Amandine; Vonheim, Emelie; Deen, Sandra; Malmros, Johan; Borgström, Birgit
Abstract: Options for fertility preservation (FP) through cryopreservation methods are currently available for young adults, adolescents, and children. Guidelines for FP have been provided by international clinical societies, and emergency procedures aimed at FP have been implemented into clinical practice worldwide. In this article, we review the current data on clinical standards of emergency FP in patients who are facing gonadotoxic effects of cancer treatment, and we also describe the methods that are still under development, usually denoted as experimental. In Sweden, programmes for FP have been established at large university hospitals, thus covering the whole country. The Swedish publicly financed health care covers both assisted reproduction for treatment of infertility and the cryopreservation of gametes or gonadal tissue when there is a medical indication, such as the risk to become infertile due to oncologic treatment; hence the access to FP is ensured for the whole population. At our centre at Karolinska University Hospital in Stockholm, methods for FP have been offered since 1988. In this article, we also review the oncologic indications for FP in our patient cohort of >3000 individuals during the period 1988–2018.